1994
DOI: 10.1111/j.1365-2672.1994.tb03037.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ELISA and RPLA for detection of Bacillus cereus diarrhoeal enterotoxin

Abstract: Fourteen strains of Bacillus cereus isolated from different sources were examined for their ability to produce diarrhoeal enterotoxin by two commercial immunoassay kits (Oxoid BCET-RPLA and Tecra ELISA) and the microslide immunodiffusion assay. One strain that was positive in monkey feedings, as well as a number of other strains isolated from diarrhoeal outbreaks, gave positive results in the ELISA and negative results in the RPLA test systems. When tested in the microslide assay, these strains produced only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 17 publications
1
17
0
2
Order By: Relevance
“…Several studies have compared the BCET-RPLA and TECRA-VIA kits for their ability to detect the B. cereus enterotoxin (5,8,19). Buchanan and Schultz reported the positive identification of 8 out of 10 and 9 out of 10 enterotoxigenic B. cereus strains by the BCET-RPLA and TECRA-VIA kits, respectively (5).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the BCET-RPLA and TECRA-VIA kits for their ability to detect the B. cereus enterotoxin (5,8,19). Buchanan and Schultz reported the positive identification of 8 out of 10 and 9 out of 10 enterotoxigenic B. cereus strains by the BCET-RPLA and TECRA-VIA kits, respectively (5).…”
Section: Discussionmentioning
confidence: 99%
“…The two were given parallel evaluations in four studies. 28,[93][94][95] BCET-RPLA (Oxoid) is the most commonly cited test method for diarrhoeal B. cereus, identified in 12 evaluative and non-evaluative studies in the wider search. Fletcher and Logan 95 compared the BCET-RPLA (Oxoid) and BDE-VIA (Bacillus diarrhoeal enterotoxin, Tecra) with an improved McCoy cell culture cytotoxicity assay.…”
Section: Diarrhoeal Strainsmentioning
confidence: 99%
“…They found the cytotoxicity assay was more sensitive than the Oxoid kit and, unlike the Tecra kit, did not give false positive results. Beecher and Wong 93 were similarly unclear as to the usefulness of the two commercial kits, although Day and colleagues 94 suggested that the Tecra kit is more reliable, having detected 87.5% (14/16) strains, compared with the Oxoid kit, which detected only 43.75% (7/16). Another study which examined foods and faeces using Tecra EIA detected the enterotoxin in seven out of 34 foods and 10 out of 15 faecal specimens from outbreaks of food poisoning.…”
Section: Diarrhoeal Strainsmentioning
confidence: 99%
“…Traditional methods to detect food-borne bacteria often rely on time-consuming growth in culture media, isolation of bacteria, biochemical identification, and sometimes serology (5,8). There have been many attempts to develop faster, more convenient, more sensitive, and more specific techniques for detection and diagnosis of pathogenic bacteria, including immunological methods, biosensors, and microarray technologies.…”
mentioning
confidence: 99%